PENGARUH PAKAN DARI AMPAS TAHU YANG DIFERMENTASI DENGAN EM4 TERHADAP PERTUMBUHAN IKAN MAS (Cyprinus carpio L.) - Rahmi, Elfia; Nurhadi, Nurhadi; Abizar, Abizar (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The main factors which can determine preserves success fishes out isÂ store feeding in quantity, quality and the right time. Artificial feeding is one of production cost which largish effort preserve fishes out. One of effort to decrease feeding cost is by using artificial feeding it self. The alternative cheap feeding but it has nutrient content that suitable with fishâs needs. One of fish meals by using waste food that can use as a feeding is tofu waste. Tofu waste is waste of tofu makings that can use as raw material of feeding fish. Raw material of feeding fish is easy to find it. We can find it in tofu company with the price cheap relative. To increase fish meals material quality from tofu waste this was done fermentations by use EM4Â (Effective Microorganisme 4). The purpose of the research is to know the effect of feeding tofu waste was done fermentations by using EM4 to growth Cyprinus carpio L. The experimental design that is Completely Randomized Design (CRD) with 4 treatment and 6 repetitions. By treatment: A (control), B (by giving tofu waste was done fermentation 10%), C (by giving tofu waste was done fermentation 16%), and D (by giving tofu waste was done fermentation 24%). Based on the research result we can conclude that tofu waste was done fermentation can increase growth Cyprinus carpio L. By giving tofu waste was done fermentation 16% with commercial feeding can get same growth if we compare with tofu waste was done fermentations 10% and 24%.Â Â